Akuntansi dalam Dunia Konten Kreator - Arya Pratama Putra; Caren; Callista, Nessya; Sherly; Putren, Irenne (Universitas Pamulang, 2025)
The development of the digital world has created new career opportunities among the younger generation, one of which is as content creators. However, most students who are interested in becoming content creators do not yet understand the importance of good financial record-keeping and management as a basis for financial decision-making. This community service activity was carried out at SMA Negeri 11 Tangerang Selatan with the aim of improving students' accounting literacy and financial awareness through training on the theme of ‘Accounting in the World of Content Creators’. The community service methods included practical training in simple transaction recording, as well as simulations of financial report preparation using case studies of content creator income. The results of the activity showed an increase in students' understanding of basic accounting concepts and their ability to manage digital finances responsibly. This activity is expected to foster financial awareness habits from an early age and prepare students to face digital economic opportunities intelligently. Keywords: accounting; content creator